Immune Responses to AAV-Vectors, the Glybera Example from Bench to Bedside - Ferreira, Valerie; Petry, Harald; Salmon, Florence (Frontiers in Immunology, 2014)
Alipogene tiparvovec (Glybera®) is an AAV1-based gene therapy that has been developed for the treatment of patients with lipoprotein lipase (LPL) deficiency. Alipogene tiparvovec contains the human lipoprotein lipase (LPL) naturally occurring gene variant LPLS447X in a non-replicating viral vector based on adeno-associated virus serotype 1 (AAV1). Such virus-derived vectors administered to humans elicit immune responses against the viral capsid protein and immune responses, especially cellular, mounted against the protein expressed from the administered gene have been linked to attenuated transgene expression and loss of efficacy. Therefore, a potential concern about the use of AAV-based vectors for gene-therapy is that they may induce humoral and cellular immune responses in the recipient that may impact on efficacy and safety. In this paper we review the current understanding of immune responses against AAV-based vectors and their impact on clinical efficacy and safety. In particular the immunogenicity findings from the clinical development of alipogene tiparvovec up to licensing in Europe will be discussed demonstrating that systemic and local immune responses induced by intramuscular injection of alipogene tiparvovec have no deleterious effects on clinical efficacy and safety. These findings show that muscle directed AAV-based gene therapy remains a promising approach for the treatment of human diseases.